Civil Infrastructure in Land Development: The Sustainable And Environmental Challenges - Abdul Ghani, A. Naser (Universiti Sains Malaysia, 2006)
Intensive housing and land development in Malaysia since the last decade has resulted in the depletion of suitable and cheap spot.